Implementasi Metode Simple Additive Weighting Dalam Sistem Pendukung Keputusan Penerima Bantuan Program Sembako - Safitri, Mulia; Sahay, Abertun Sagit; Lestari, Ariesta (Journal of Information Technology and Computer Science, 2021)
Pahandut Seberang Village has an average middle to the lower level of economy in the community, so most of the people still need assistance from the government. In Pahandut Seberang Village, the selection of recipients of the Smbako program assistance is still the old way by using from paper. The assessment process is still not transparent in nature and the selection process is very slow and receipt of Sembako programs assistance are not being on target. Therefore, to overcome this problem, a Decision Support System (SPK) is created to help the Pahandut Seberang Village in selecting the recipients prospective of Sembako program assistance In designing and building the system are using 2 development methods, namely the Waterfall method as a software development method and the Simple Additive Weighting (SAW) method as a decision support system method in its calculations. Where the saw method has 4 stages, namely determining the criteria, determining the suitability, making a decision matrix based on the criteria and normalizing the. The final result is obtained from the ranking, namely the sum of the normalized matrix multiplication R with the weight vector so that the largest value sas a solution. This system testing uses a Black-box testing system. The test results show that the system created has been running according to the expectations of the researcher. This research produces a decision support system for selection of the recipients prospective that can provide recommendations for the recipients prospective the Pahandut Seberang village.